Should I Drop Out of School? A Study of the Right to Education For Pregnant Students - Ratih Lestarini (Yuridika, 2023)
Every Indonesian child has the right to a proper education, including pregnant students. In reality, solving the problem of pregnant students often ends with the dismissal of the children from school either directly or by resignation. Instead of providing protection, the school sanctions children who are considered to damage the image of the school as a moral educational institution, actually the school has neglected their basic rights, namely proper education guaranteed by the state through the constitution and laws related to education. Therefore, the purpose of this paper is to explain the above problems studied from the perspective of child protection on the basis of the principle of the best interests of the child. The method used in this research is the socio-legal method, which analyzes the implementation of education policy. The results of this study indicate that there are no guidelines for resolving cases of students who become pregnant during their study period. The settlement is left to the school, which usually ends with a decision from the school to expel the student on the basis of educational morals and school image. This is contrary to the guarantee of the right to education for every Indonesian citizen child as mandated in education law, especially regarding the 12-year compulsory education policy.